Analisis Kemampuan Pemecahan Masalah Sistem Persamaan Linier Tiga Variabel Berdasarkan Disposisi Matematis - Siti Fatimatus Sahro; wildan hakim (Kilau Publishing, 2024)
Problem solving is an ability that students must have. When learning mathematics, students often have difficulty solving problems that are different from the examples given by the teacher. This research aims to describe the problem-solving abilities of Systems of Linear Equations with Three Variables (SPLTV) in terms of students' mathematical disposition. The research method used was descriptive, with a sample consisting of 36 students. The subjects of this research were three people selected from the high, medium and low categories based on the results of a mathematical disposition questionnaire. The selected subjects were given SPLTV problem solving ability questions. Data collection techniques applied in this research include mathematical disposition questionnaires, tests, documentation and interviews. The research results showed that the majority of subjects showed a moderate level of disposition. (2) Subjects with low and medium dispositions experience difficulty in evaluating the problems given, which hinders their ability to proceed to the next step. (3) Subjects with a high level of disposition almost fulfill all indicators of problem-solving ability.